ANALISIS SISTEM PENGELOLAAN KEUANGAN DAN KINERJA PERBENDAHARAAN - Alfret Genus Waray; Sita Yubelina Sabandar; Atus Buku (Paulus Journal of Accounting (PJA), 2024)
This study analyzes the financial management system and treasury performance at the Teluk Kimi District Office, Nabire Regency. Using a qualitative approach, data were collected through observation, interviews, and documentation with seven informants who understand the financial management and treasury system. The results of the study indicate that the financial management system has been well structured through planning, implementation, supervision, and reporting that are oriented towards transparency and accountability. Treasury performance is evaluated based on indicators of timeliness of reporting, accountability of budget use, quality of financial reports, and audit results. The main supporting factors include leadership support, staff quality, clear regulations, and utilization of technology. However, challenges such as budget constraints, lack of transparency, suboptimal coordination, and resistance to change still need to be addressed. Key recommendations include increasing human resource capacity, implementing more transparent reporting mechanisms, and optimizing information technology to improve the efficiency and effectiveness of financial management. This study contributes to strengthening regional financial governance by highlighting the importance of the role of stakeholders in improving accountability and transparency in public budget management.